Directional soaking composite honeycomb structure and manufacturing method thereof
By introducing a directional heat homogenization layer and core filler into the honeycomb structure, the problem of insufficient heat dissipation in traditional honeycomb structures in high temperature environments is solved, and better thermal stability and heat resistance are achieved.
Patent Information
- Application Number
- CN202410640966.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-22
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-05-22
AI Technical Summary
Traditional honeycomb structures have insufficient heat dissipation performance in high-temperature environments, resulting in severe local heat exposure, which poses a potential risk of insufficient high-temperature application performance.
A directional homogenized composite honeycomb structure is designed, including a directional homogenized layer, upper skin, honeycomb core, core filler, and lower skin. The directional heat homogenization layer is made of a two-dimensional material basis, which can conduct heat transversely to avoid heat accumulation; the filler inside the honeycomb core hinders heat conduction and radiation, and improves heat capacity.
Through the design of the directional heat homogenization layer, the accumulation and accumulation of heat on the surface is effectively avoided, the effective heat input in the heat concentration area on the honeycomb surface is reduced, and the thermal stability is improved; the filler inside the honeycomb core increases the heat capacity, reduces the heat transfer amount, and enhances heat resistance.
Smart Images

Figure CN119855100A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of honeycomb structures, and in particular to a directional heat-homing composite honeycomb structure and a manufacturing method thereof. Background Art
[0002] With the development of aviation and aerospace, it is necessary to develop a new type of structure with better comprehensive performance. At this time, the honeycomb structure has attracted the attention of scholars with its good mechanical properties, light weight, heat insulation, sound insulation and other characteristics. Due to its high price, the honeycomb structure was initially only used in the aerospace field. However, with the continuous advancement of technology and the continuous development of the national economy, the honeycomb structure has gradually turned to civilian use. In the past decade, honeycomb structures have been used in transportation, construction, energy, packaging and other fields. In these fields, the honeycomb structure is used as a structural and lightweight material, that is, it reduces the overall quality of the device while also providing better mechanical properties. Due to the needs of engineering applications, higher and more requirements are also put forward for the performance of the honeycomb structure, such as higher mechanical properties and thermal insulation properties.
[0003] Most honeycomb structures currently used use a single honeycomb structure (upper and lower skins and a middle honeycomb core) to achieve overall lightweighting of the structure, which can meet the lightweight and ambient temperature application requirements under certain working conditions. This single honeycomb structure has certain heat resistance, but in certain high temperature environments, especially when subjected to relatively concentrated heat, it will cause local high temperature accumulation, posing the risk of insufficient high temperature application performance. Summary of the invention
[0004] In view of the above analysis, the present invention aims to provide a directional heat-isolating composite honeycomb structure and a manufacturing method thereof, so as to solve the problem of severe local heating caused by insufficient heat dissipation performance of the traditional honeycomb structure in practical applications.
[0005] The purpose of the present invention is mainly achieved through the following technical solutions:
[0006] On the one hand, the present invention designs a directional heat-isolating composite honeycomb structure, including a directional heat-isolating layer, an upper skin, a honeycomb core and core filler, and a lower skin arranged in sequence from top to bottom.
[0007] Furthermore, the directional heat-dissipating layer is made of a two-dimensional material base, including but not limited to ceramic materials, high thermal conductivity graphene films, graphene-based composite materials, and graphene-based ceramic composite materials, with a thickness of 0.01 to 10 mm.
[0008] Furthermore, the upper skin is one of titanium-based and nickel-based alloys, and has a thickness of 0.1 mm to 20 mm.
[0009] Furthermore, the lower skin is one of titanium-based and nickel-based alloys, and has a thickness of 0.1 mm to 20 mm.
[0010] Furthermore, the honeycomb core is a honeycomb-like grid structure with a thickness of 0.01 to 3 mm, a height of 1 to 50 mm, and is made of titanium alloy.
[0011] Furthermore, the core filler has a density less than 1g / cm 3 One of the silicon-based fibers, silicon-based aerogels or graphene aerogels.
[0012] On the other hand, the present invention also provides a method for manufacturing a directional and uniformly heated composite honeycomb structure, which is used to manufacture the directional and uniformly heated composite honeycomb structure, comprising the following steps:
[0013] S1. Perform surface treatment by laying or brushing one or more layers of brazing material on the lower skin;
[0014] S2. Use vacuum brazing or gas shielded brazing to first weld the honeycomb core and the lower skin together;
[0015] S3, filling the honeycomb core filler into the honeycomb core mechanically and / or manually;
[0016] S4. Perform surface treatment by laying or brushing one or more layers of brazing material on the upper skin;
[0017] S5, welding the upper skin and the honeycomb core together to obtain a honeycomb structure;
[0018] S6. Preparing a two-dimensional material-based directional heat-saturating layer on the outer surface of the honeycomb structure upper skin by spraying, brazing or bonding;
[0019] S7. After the final welding of the components is completed, the whole is subjected to stabilization heat treatment.
[0020] Furthermore, in step S1 or S4, the thickness of the solder layer is 0.01 to 3.5 mm.
[0021] Furthermore, in step S5, the welding temperature is 450-1400° C., and the holding time is 20-60 min.
[0022] Furthermore, in step S6, the spraying method includes flame spraying, plasma spraying, cold spraying, etc.; the spraying method is used to spray the directional heat-averging material onto the upper skin, and the spraying temperature is 800-1200°C (excluding cold spraying), and curing treatment is also required, and the curing temperature is 25-450°C and the curing time is 0-180min; when the welding method is used, the brazing temperature is 800-960°C, the insulation time is 10-45min, and Ti-Cu-Ag type brazing material is used; when the bonding method is used, high-temperature resistant inorganic glue is used, and the glue is evenly applied to the bonding surface, first placed at room temperature for 2-12 hours, then kept at a temperature of 60-100°C for 1-4 hours, and then continued to be kept at 100-300°C for 2 hours to complete the bonding.
[0023] Furthermore, in step S7, the stabilization heat treatment temperature is 20-100° C. lower than the welding temperature.
[0024] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0025] a) Directional heat dissipation function and high thermal stability: Based on a single honeycomb structure, the present invention adds a directional heat-averaging layer on the surface. This structure can conduct heat laterally to the low temperature area, thus avoiding the gathering and accumulation of heat on the surface to a great extent, reducing the input of effective heat per unit area in the heat concentration area on the honeycomb surface, making the surface energy distribution more uniform, and preventing part of the heat from being conducted to the inside of the honeycomb, thereby effectively solving the problem of severe local heating caused by insufficient heat resistance of the honeycomb structure during actual application, thereby effectively improving the thermal stability of the honeycomb structure.
[0026] b) High heat capacity and good heat resistance: Based on a single honeycomb structure, the present invention adds a core filler inside the honeycomb core, which can effectively hinder the conduction and radiation of heat inside the honeycomb, improve the heat capacity of the honeycomb structure, and thus reduce the effective transfer of honeycomb heat from the hot end to the cold end. It can effectively achieve secondary control of the imported heat, avoid overheating failure due to excessive imported heat, and improve the heat resistance of the overall structure.
[0027] c) High interlayer bonding strength and high mechanical properties: The present invention improves the reliability of the connection through the combined optimization of the brazing material and the brazing process, and satisfies and realizes the welding between the skin and the honeycomb core made of different titanium alloys. Before welding the honeycomb core and the skin, and before welding the honeycomb skin and the directional heat-absorbing layer, surface treatment is performed, and then vacuum diffusion welding or vacuum brazing or brazing under a protective atmosphere is performed. After the final welding of the components is completed, the whole is subjected to a stabilization heat treatment to improve the interlayer bonding strength, thereby effectively improving the mechanical properties of the honeycomb structure.
[0028] d) The oriented heat-averaging layer of the present invention can adopt highly oriented and high-density ceramic materials. The highly oriented and high-density ceramics can adopt any two or more raw materials of small-particle high-oriented ceramic powder, large-particle high-oriented ceramic powder and graphene oxide aqueous solution, such as a compound of small-particle high-oriented ceramic powder and large-particle high-oriented ceramic powder, or a compound of small-particle high-oriented ceramic powder and graphene oxide aqueous solution, or a compound of large-particle high-oriented ceramic powder and graphene oxide aqueous solution, or a compound of large-particle high-oriented ceramic powder, small-particle high-oriented ceramic powder and graphene oxide aqueous solution; finally, a bonding agent is added to improve the orientation and density of the green embryo structure during the molding process, so as to enhance the high orientation and excellent performance of the ceramic material finally obtained.
[0029] The present invention adopts a compound of small-particle high-oriented ceramic powder and large-particle high-oriented ceramic powder, and controls the ratio between the two, and selects high-oriented ceramic powders with different orientation forms (such as fibrous, columnar, and lamellar) and different particle sizes, so as to obtain highly oriented and high-density ceramics with higher density and mechanical strength.
[0030] When the present invention uses small-particle-size high-oriented ceramic powder or large-particle-size high-oriented ceramic powder and mixes it with a graphene oxide aqueous solution, the orientation of the ceramic and the performance of the ceramic can be optimized.
[0031] The present invention adopts small-particle high-oriented ceramic powder and large-particle high-oriented ceramic powder and then mixes them with graphene oxide aqueous solution, and with the assistance of bonding additives, strictly controls the particle size and weight ratio of the high-oriented ceramic, and fills the gaps between the large-particle high-oriented ceramic powders with small particles, thereby improving the density of the ceramic; utilizes the orientation preference of the large-particle high-oriented ceramic powder in the stacking process to optimize the orientation of the ceramic, and the large-particle high-oriented ceramic powder acts as a "structural bridge" between the small-particle high-oriented ceramic powder and the bonding additive, greatly improving the mechanical strength of the ceramic.
[0032] The preparation method of the highly oriented and high-density ceramics of the present invention further optimizes the orientation of the mixed powder during drying by designing a powder mixing method, introducing graphene oxide and vacuum filtration. The highly oriented ceramics prepared by this method have a lower porosity than ceramics prepared by traditional methods, and can still exhibit excellent material properties even under pressureless sintering conditions, such as ultra-high in-plane thermal conductivity and ultra-high bending strength.
[0033] Other features and advantages of the present invention will be described in the following description, and some advantages may become apparent from the description, or may be understood by practicing the present invention. The purpose and other advantages of the present invention may be realized and obtained through the contents particularly pointed out in the description and the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0035] Figure 1 This is a schematic diagram of a directional, heat-equilibrated composite honeycomb structure in an embodiment of the present invention;
[0036] Figure 2 This is a back temperature test diagram of the ceramic of Preparation Example 6 and Comparative Example 1 using Example 3 of the present invention;
[0037] Figure 3 This is a scanning electron microscope photo of the ceramic fracture obtained in Preparation Example 3 of the present invention;
[0038] Figure 4 This is a scanning electron microscope photo of the ceramic fracture obtained in Preparation Example 2 of the present invention;
[0039] Figure 5 This is a scanning electron microscope photo of the ceramic fracture obtained in Preparation Example 1 of the present invention;
[0040] Figure 6 This is a scanning electron microscope photo of the ceramic fracture obtained in Preparation Example 4 of the present invention;
[0041] Figure 7 This is a scanning electron microscope photograph of the ceramic fracture obtained in Preparation Example 7 of the present invention;
[0042] Figure 8 This is a scanning electron microscope photograph of the ceramic fracture obtained in Preparation Example 8 of the present invention.
[0043] Reference numerals:
[0044] 11-upper skin; 12-lower skin; 2-honeycomb core; 3-directional heat-isolating layer; 4-core filling. DETAILED DESCRIPTION
[0045] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.
[0046] On the one hand, the present invention designs a directional heat-isolating composite honeycomb structure, such as Figure 1 As shown, it includes: an upper skin 11, a lower skin 12, a honeycomb core 2, a directional heat-isolating layer 3, and a core filler 4.
[0047] Specifically, the oriented heat-dissipating layer is prepared from two-dimensional material-based materials, including but not limited to ceramic materials, high thermal conductivity graphene films, graphene-based composite materials, and graphene-based ceramic composite materials, with a thickness of 0.01 to 10 mm.
[0048] It should be noted that the directional heat-saturating layer is at the outermost layer, which can largely avoid the accumulation of heat on the surface, conduct the heat laterally to the low-temperature area, and reduce the effective heat input per unit area in the heat-concentrated area of the honeycomb surface. Concentrated heat distribution often causes local heating of the structure and harms the performance of the structure. The directional heat-saturating layer can conduct heat to the surrounding low-temperature area, making the heat distribution area on the structure wider, while also increasing heat dissipation and effectively avoiding heat accumulation.
[0049] Specifically, the upper skin is one of titanium-based and nickel-based alloys, and has a thickness of 0.1 mm to 20 mm.
[0050] Specifically, the lower skin is one of titanium-based and nickel-based alloys, and has a thickness of 0.1 mm to 20 mm.
[0051] In a possible implementation, TA15 titanium alloy is used as the upper and lower skins of the directional heat-saturated composite honeycomb structure. TA15 titanium alloy is a near-α-type titanium alloy with a high Al equivalent. Its main strengthening mechanism is to add the α-stabilizing element Al for solid solution strengthening, and to add the neutral element Zr and the β-stabilizing elements Mo and V for supplementary strengthening and improved process performance. Therefore, the alloy has both the good thermal strength and weldability of the α-type titanium alloy and the process plasticity of the (α+β)-type titanium alloy, and is particularly suitable for manufacturing various welded parts.
[0052] Specifically, the honeycomb core is a honeycomb-like grid structure with a thickness of 0.01 to 3 mm, a height of 1 to 50 mm, and is made of titanium alloy.
[0053] It should be noted that aerospace equipment will generate a lot of heat during high-speed flight due to friction with the air. The impact of this large amount of highly concentrated heat is an issue that must be considered in modern and future high-precision manufacturing industries. Titanium alloys are often used in the aerospace field due to their excellent high-temperature performance and high specific strength. Therefore, titanium alloys can be used for the upper and lower skins and honeycomb cores.
[0054] Specifically, the core filler has a density less than 1g / cm 3 One of the silicon-based fibers, silicon-based aerogels or graphene aerogels.
[0055] In a possible embodiment, the silicon-based fiber is a silica fiber, and the silica fiber is used as a core filler, and the density is controlled by controlling the ratio of the mass and volume of the silica fiber. The length of the silica fiber is 10.00-11.00 mm, and the diameter is 1-100 μm. Silica fiber has a low thermal conductivity and a high thermal resistance, is pollution-free, and has stable physical and chemical properties. As a core filler of a honeycomb structure, it can increase the heat capacity of the structure as a whole, can effectively prevent the conduction of the internal airflow and the heat transfer effect of the convection effect, increase the heat capacity of the structure, and effectively reduce internal heat transfer.
[0056] In one possible embodiment, the silicon-based aerogel is a silicon dioxide aerogel with a specific surface area of 300-1500m 2 / g, the average pore size is 6 to 10nm, and the porosity reaches 80% of the total structure, which reduces the radiation heat transfer between the inner surfaces of the honeycomb and the convection heat transfer of the air in the core.
[0057] In one possible embodiment, the core filler is graphene aerogel, and the density of the graphene aerogel is less than 1g / cm 3 , with a specific surface area of 2630m 2 / g, it has excellent thermal insulation performance among the components of vacuum structures, and its abundant internal cavities can reduce the conduction of heat, thereby improving the thermal insulation performance of the structure.
[0058] It should be noted that the core filling inside the honeycomb can effectively hinder the conduction and radiation of heat inside the honeycomb, improve the thermal capacity of the honeycomb structure, thereby reducing the effective transfer of honeycomb heat from the hot end to the cold end, and can effectively achieve secondary control of the imported heat, avoiding overheating and failure of the protected device due to excessive imported heat.
[0059] The directional heat-saturating layer is made of a two-dimensional material base, including but not limited to ceramic materials, high thermal conductivity graphene films, graphene-based composite materials, and graphene-based ceramic composite materials, with a thickness of 0.01 to 10 mm. The directional heat-saturating layer can be formed on the outer surface of the honeycomb structure skin by spraying, brazing or bonding.
[0060] Furthermore, the high thermal conductivity graphene film is a graphene high thermal conductivity film with a thickness of 100 to 400 μm. The film is made of graphene as a raw material and is formed by stacking multiple layers of graphene. The thermal conductivity coefficient is greater than 1000 W / m·K.
[0061] Furthermore, the ceramic material is a high-orientation and high-density ceramic material, and the preparation raw materials include any two or more raw materials of small-particle high-orientation ceramic powder, large-particle high-orientation ceramic powder and graphene oxide aqueous solution, and a bonding aid; wherein the small-particle high-orientation ceramic powder and the large-particle high-orientation ceramic powder are selected from α-Al2O3, hBN, SiC, layered molybdate, Si3N4 and SiO2; the bonding aid is selected from yttrium oxide, magnesium oxide, aluminum oxide, silicon dioxide and mullite.
[0062] Compared with the prior art, the high-orientation and high-density ceramics provided by the present invention adopt any two or more raw materials of small-particle high-oriented ceramic powder, large-particle high-oriented ceramic powder and graphene oxide aqueous solution, such as a compound of small-particle high-oriented ceramic powder and large-particle high-oriented ceramic powder, or a compound of small-particle high-oriented ceramic powder and graphene oxide aqueous solution, or a compound of large-particle high-oriented ceramic powder and graphene oxide aqueous solution, or a compound of large-particle high-oriented ceramic powder, small-particle high-oriented ceramic powder and graphene oxide aqueous solution; finally, a bonding agent is added to improve the orientation and density of the green embryo structure during the molding process, so as to enhance the high orientation and excellent performance of the ceramic material finally obtained.
[0063] It should be noted that the small-particle high-orientation ceramic powder and large-particle high-orientation ceramic powder of the present invention are selected from materials with orientation, such as one-dimensional fiber or rod; two-dimensional lamellar, such as lamellar α-Al2O3, lamellar hexagonal boron nitride (hBN), etc.
[0064] Specifically, the mass ratio of the small-particle high-oriented ceramic powder and / or the large-particle high-oriented ceramic powder to the bonding aid is 100:(0-40), such as 100:1, 100:10, 100:20, 100:30 or 100:40.
[0065] It should be noted that the bonding aid in the present invention is used in combination with highly oriented ceramic powder to prepare ceramics, and the type of bonding aid affects the properties of the final ceramics. When the bonding aid is selected as alumina, the resulting ceramics have higher thermal conductivity; when the bonding aid is selected as mullite, the resulting ceramics have higher hardness; when the bonding aid is selected as a mixture of alumina, magnesium oxide and mullite, the resulting ceramics have both better thermal conductivity and higher mechanical strength.
[0066] The present invention can select different bonding aids according to different usage scenarios of the ceramics, such as usage scenarios with high thermal conductivity requirements and low mechanical property requirements; or high thermal conductivity and mechanical property requirements; or high mechanical property requirements and low thermal conductivity. The overall solution is simple and relatively flexible.
[0067] Furthermore, the mass ratio of the small-particle highly oriented ceramic powder and / or the large-particle highly oriented ceramic powder to the graphene oxide aqueous solution is 10:1-200:1, such as 10:1, 20:1, 40:1, 50:1, 70:1, 80:1, 100:1, 120:1, 150:1, 180:1 or 200:1.
[0068] Specifically, the diameter of the graphene oxide sheets in the graphene oxide aqueous solution is ≥5 μm.
[0069] Specifically, the concentration of the graphene oxide aqueous solution is 0.5 mg / ml-10 mg / ml, such as 0.5 mg / ml, 1.5 mg / ml, 2.5 mg / ml, 5 mg / ml, 7 mg / ml or 10 mg / ml.
[0070] It should be noted that during the preparation of ceramics, an aqueous solution of graphene oxide (GO solution for short) was added to reduce the van der Waals force (repulsive force) between highly oriented ceramic powders, optimize their arrangement structure, and make the highly oriented ceramic powders and bonding aids more evenly dispersed. Combined with vacuum filtration, the resulting ceramic surface structure is smoother, especially for boron nitride ceramics.
[0071] When the mass of highly oriented ceramic powder is less than 10 times the mass of graphene oxide, the graphene content is too high, affecting the material's temperature resistance; when the mass of highly oriented ceramic powder is higher than 200 times the mass of graphene oxide, the graphene content is too low and cannot play a role in regulating the ceramic arrangement structure and optimizing the structural mechanical properties.
[0072] Specifically, the average particle size of the large-particle-size high-oriented ceramic powder is 10-30 times the average particle size of the small-particle-size high-oriented ceramic powder.
[0073] Specifically, the average particle size of the large-particle-size and highly-oriented ceramic powder is 80-500 μm.
[0074] It should be noted that in the present invention, large-particle high-oriented ceramic powder and small-particle high-oriented ceramic powder can be compounded, and the particle size and weight ratio of large-particle high-oriented ceramic powder and small-particle high-oriented ceramic powder can be further controlled and optimized. The small-particle high-oriented ceramic powder is used to fill the gaps between the large-particle high-oriented ceramic powders, thereby improving the density of the ceramics. The orientation preference of the large-particle high-oriented ceramic powder during the stacking process is utilized to optimize the orientation of the ceramics, and the large-particle high-oriented ceramic powder can act as a "structural bridge" between the small-particle high-oriented ceramic powder and the bonding aid, greatly improving the mechanical strength of the ceramics.
[0075] Specifically, the mass ratio of the large-particle-size high-oriented ceramic powder to the small-particle-size high-oriented ceramic powder is 1:1-1:35.
[0076] Preferably, the average particle size of the large-particle-size and highly-oriented ceramic powder may be 80 μm, 120 μm, 200 μm, 350 μm or 500 μm.
[0077] Preferably, the average particle size of the small-particle-size and highly-oriented ceramic powder may be 2 μm, 8 μm, 12 μm, 25 μm or 50 μm.
[0078] The present invention needs to regulate the mass ratio of large-particle-size high-oriented ceramic powder and small-particle-size high-oriented ceramic powder, and control the mass of small-particle-size high-oriented ceramic powder to be 1-35 times that of large-particle-size high-oriented ceramic powder.
[0079] Preferably, the mass of the small-particle highly oriented ceramic powder is 1 times, 2 times, 4 times, 6 times, 10 times, 15 times, 18 times, 22 times, 25 times, 30 times or 35 times that of the large-particle highly oriented ceramic powder.
[0080] Preferably, the mass of the small-particle-size highly-oriented ceramic powder is 1-10 times that of the large-particle-size highly-oriented ceramic powder.
[0081] According to simulation and experimental results, as the content of large-particle-size, highly oriented ceramic powder decreases, the resulting orientation gradually decreases. The larger the absolute value of IOP, the higher the orientation of the material.
[0082] Specifically, the bonding aids include yttrium oxide, magnesium oxide, aluminum oxide, silicon dioxide and mullite.
[0083] Specifically, the particle size of the bonding aid is smaller than or equal to the average particle size of the selected small-particle-size and highly-oriented ceramic powder.
[0084] It should be noted that the large-particle-size high-oriented ceramic powder in the present invention serves as a bridge connecting the small-particle-size high-oriented ceramic powder and the bonding agent, and the bonding agent particle size is regulated to be less than or equal to the average particle size of the small-particle-size high-oriented ceramic powder. When the bonding agent particle size is small, it can fill in the gaps and increase the density and strength of the final ceramic.
[0085] Furthermore, the preparation method of the highly oriented and highly dense ceramic material comprises the following steps:
[0086] S1: Weigh large-particle-size high-oriented ceramic powder and small-particle-size high-oriented ceramic powder according to proportion and mix them with solvent respectively, with the mixing ratio being 10g:1L;
[0087] Then, any two or more of the mixed large-particle-size high-oriented ceramic powder solution, small-particle-size high-oriented ceramic powder solution and graphene oxide aqueous solution are mixed;
[0088] S2: Weigh the bonding agent according to the proportion and mix it with the solvent, the mixing ratio is 10g:1L;
[0089] S3: Mix the mixed solution prepared in S1 and S2, stir, and then use vacuum filtration to obtain a dry mixed powder block, and transfer the mixed powder block to a sintering mold;
[0090] S4: placing the mold in a heating furnace and drying it at 100-600° C. for 0.5-2 hours to obtain a ceramic green body;
[0091] S5: Sintering the obtained ceramic green body to obtain a highly oriented and high-density ceramic.
[0092] Compared with the prior art, the present invention adopts a compound of large-particle-size high-oriented ceramic powder and small-particle-size high-oriented ceramic powder, which can improve the orientation of ceramic green body and final ceramic; or add graphene oxide aqueous solution to large-particle-size high-oriented ceramic powder and / or small-particle-size high-oriented ceramic powder, and cooperate with vacuum filtration means, which can improve the orientation and performance of ceramic green body and final ceramic.
[0093] Before sintering, the mixed powder block needs to be dried at 100-600°C. When graphene oxide aqueous solution is used, it is dried at 100-500°C in order not to affect the material content. However, when there is residual graphene oxide aqueous solution during the preparation process, it is dried at 500-600°C for 0.5-1h. Graphene will undergo aerobic oxidation in an environment above 500°C, converted into carbon dioxide and discharged, and the residual graphene oxide is removed.
[0094] By adopting the preparation method of the highly oriented ceramic material of the present invention, the porosity of the obtained ceramic green body is lower than that of the ceramic powder green body prepared by the traditional method (pressing), and the obtained ceramic still has excellent properties even under pressureless sintering conditions, such as ultra-high in-plane thermal conductivity, ultra-high flexural strength, etc. For example, when preparing alumina ceramics, the flexural strength is above 190.67MPa; when preparing hexagonal boron nitride ceramics, the axial thermal conductivity is above 12.05W / m·K, and the radial thermal conductivity is above 12.05W / m·K.
[0095] Specifically, the solvent includes, but is not limited to, one or more of water, methanol, ethanol, ethylene glycol, isopropanol, butylpentane, dimethylformamide, acetone, and tetrahydrofuran.
[0096] It should be noted that adding a solvent to the large-particle high-oriented ceramic powder and / or the small-particle high-oriented ceramic powder in the present invention can make them disperse better without causing agglomeration problems. For example, hBN disperses better in isopropanol than in water.
[0097] Specifically, in step S6, the sintering is performed by pressure sintering or pressureless sintering, and the sintering temperature is 1750-2000°C.
[0098] Specifically, during pressure sintering, the pressure is 5MPa-40MPa.
[0099] On the other hand, the present invention provides a method for manufacturing a directional and heat-equilibrated composite honeycomb structure, which is used to manufacture the directional and heat-equilibrated composite honeycomb structure, comprising the following steps:
[0100] S1. Perform surface treatment by laying or brushing one or more layers of brazing material on the lower skin;
[0101] S2. Use vacuum brazing or gas shielded brazing to first weld the honeycomb core and the lower skin together;
[0102] S3, filling the honeycomb core filler into the honeycomb core mechanically and / or manually;
[0103] S4. Perform surface treatment by laying or brushing one or more layers of brazing material on the upper skin;
[0104] S5, welding the upper skin and the honeycomb core together to obtain a honeycomb structure;
[0105] S6. Prepare a ceramic-based, graphene-based or silicon-based directional heat-absorbing layer on the outer surface of the honeycomb structure skin by spraying, brazing or bonding;
[0106] S7. After the final welding of the components is completed, the whole is subjected to stabilization heat treatment.
[0107] Specifically, in step S1 or S4, the brazing filler metal is a thin strip brazing filler metal produced by vacuum quenching technology, and the composition is titanium-based, i.e., Ti-Zr-Cu-Ni. The thickness of the brazing filler metal layer is 0.01-3.5 mm, such as 0.01 mm, 0.05 mm, 0.1 mm, 1 mm, 1.5 mm, 2 mm, 3 mm, and the surface roughness Ra during welding can be controlled within the range of 0.4-0.6. The appropriate roughness will obtain a better capillary effect, so that the molten brazing filler metal can better wet the substrate, thereby improving the brazing quality.
[0108] Specifically, the welding process in step S2 is 33-60°C lower than the phase transition point temperature of the titanium-based alloy system, and the connection is performed in a vacuum diffusion brazing furnace, and the welding rate reaches more than 90%. The appropriate welding temperature can ensure the welding quality. Too low a temperature may cause the brazing material to not melt completely, and too high a temperature may cause the matrix to undergo a phase change and damage the overall structural performance.
[0109] Specifically, in step S3, the silica fibers are clustered as core fillers and stuffed into the honeycomb core. During the stuffing process, the height and other dimensions of the fillers are controlled to be larger than the size of the honeycomb core by 0.1 to 1 mm, thereby reducing the relative sliding between the internal filler and the honeycomb structure, that is, the size of the filler must be adapted to the internal size of the honeycomb grid.
[0110] Specifically, in step S5, the welding temperature is 450-1400°C, such as 600°C, 750°C, 900°C, 920°C, 930°C, 940°C, 960°C, 970°C, 1100°C, 1300°C, and the insulation time is 20-60 min.
[0111] Specifically, in step S6, the spraying method includes flame spraying, plasma spraying, and cold spraying.
[0112] It should be noted that when the directional heat-saturating material is sprayed onto the upper skin by spraying, the upper skin surface needs to be treated before spraying to control the roughness within the range of 0.04 to 0.2. Subsequently, the oil and small particles on the upper skin surface are cleaned by alkaline washing, and then evenly sprayed, and the spraying temperature is 800 to 1200°C (excluding cold spraying).
[0113] After spraying, curing treatment is required to make the connection between the material and the skin stronger. The curing temperature is 25-450°C and the curing time is 0-180 minutes.
[0114] In one possible implementation, the two-dimensional ceramic material is sprayed onto the TA15 panel by cold spraying: before spraying, the TA15 panel is first polished with 800# sandpaper to remove the oxide scale, and the roughness Ra is controlled within the range of 0.04 to 0.2 during polishing, and then the oil stains and small particles on the surface of the TA15 panel are cleaned by alkaline washing.
[0115] For the graphene-based composite material, the spraying raw material is a dispersed solution of the graphene-based composite material, wherein the dispersed solution is deionized water, and the mass concentration of the graphene-based composite material is 280-300 mg·L -1 ; Then preheat at 50℃ and spray at a speed of 700mm / s. After spraying, curing is required to make the connection between the graphene-based composite material layer and the TA15 panel more solid and reliable. The curing temperature is 150-450℃ and the curing time is 30min.
[0116] For graphene-based ceramic composite materials, graphene is dispersed in a dispersion medium to form a graphene dispersion with a concentration of 5%, and SiO2 ceramic powder is added to the graphene dispersion with a solubility of 280-350 mg·L -1, mixed evenly, where the spraying raw material is a mixed dispersion of graphene and SiO2 ceramic powder, the dispersion medium is deionized water, the powder particle size is 100-200μm, and then preheated at 60℃ for spraying, the spraying temperature is 800℃, and the spraying speed is 500mm / s. After spraying, it is also necessary to perform curing treatment to make the connection between the two-dimensional graphene-based ceramic composite material layer and the TA15 panel more solid and reliable. The curing temperature is 150-450℃, and the curing time is 30min.
[0117] Specifically, in steps S1 and S4, when brazing is adopted, the brazing temperature is 800-960° C., the holding time is 10-45 min, and Ti-Zr-Cu-Ni type brazing material is used.
[0118] Specifically, in step S6, when brazing is adopted, the brazing temperature is 800-960° C., the holding time is 10-45 min, and Ti—Cu—Ag type brazing material is used.
[0119] In a specific embodiment of the present invention, a prepared ceramic material with a thickness of 0.1 mm is connected to an upper skin by brazing. First, the upper skin is polished to remove the surface oxide film using 800# sandpaper, and a layer of evenly ground Ti-Cu-Ag brazing powder is spread on it. The directional heat-absorbing layer of the ceramic material is placed on the top layer, and a single-layer graphite pressing plate with a mass of 5 kg is added to apply a load. Then, the ceramic material is placed in a vacuum brazing furnace and the vacuum degree is 8×10 -4 Pa, welding temperature is 890℃, holding time is 15min. Then it is lowered to 800℃, held for 5min, and cooled with the furnace until it is out of the furnace.
[0120] Specifically, in steps S1 and S6, when the bonding method is adopted, a high temperature resistant inorganic glue is used, and the glue is evenly applied to the bonding surface, first placed at room temperature for 2 to 12 hours, then maintained at a temperature of 60 to 100°C for 1 to 4 hours, and then continued to be maintained at 100 to 300°C for 2 hours to complete the bonding.
[0121] In a specific embodiment of the present invention, a high thermal conductivity graphene film is bonded to a TA15 panel by bonding: the adjusted high temperature resistant inorganic glue is evenly applied between the TA15 panel and the graphene film with a thickness of 0.1 mm, first placed at room temperature for 2 hours, then maintained at a temperature of 60°C for 1 hour, and then continued to be maintained at 100°C for 2 hours to complete the bonding.
[0122] Specifically, in step S7, the stabilization heat treatment temperature can be 20-100°C lower than the welding temperature. In order to stabilize the weld structure during the welding process, a scanning electron microscope can be used for detection to ensure that the elements in each process of the structural connection are fully diffused and the stress can be eliminated.
[0123] In order to describe the present invention more clearly, the following examples and comparative examples are used to further illustrate the present invention. Each example and comparative example uses a 1 mm thick TA15 skin, a honeycomb core with a wall thickness of 0.1 mm and a height of 10 mm, and uses Ti-Zr-Cu-Ni brazing material.
[0124] Example 1
[0125] A directional heat-averaging composite honeycomb structure comprises a directional heat-averaging layer 3, an upper skin 11, a honeycomb core 2 and a core filler 4, and a lower skin 12 which are arranged in sequence from top to bottom, wherein the directional heat-averaging layer 3 is a high thermal conductivity graphene film with a thickness of 0.1 mm, the thickness of the upper skin 11 and the lower skin 12 are both 1 mm, the size of the honeycomb core 2 is a height of 10 mm and an inscribed circle diameter of 10 mm, and the filling amount of the core filler 4 is filled by volume according to the specific density.
[0126] Preparation of directional heat-saturated composite honeycomb structure:
[0127] Use 1000# sandpaper to grind the lower skin and one side of the honeycomb core to control the roughness within the range of 0.4-0.6, then spread the brazing material between the two. The brazing material is Ti-Zr-Cu-Ni. The welding is completed under vacuum conditions. The welding process is selected at 920℃ and the holding time is 20min. Then, the stabilization heat treatment is carried out at 900℃ and the holding time is 20min. The adjusted density is 0.8g / cm 3 The silica fiber is filled into the honeycomb core, the height of the honeycomb core is 10mm, the length of the silica fiber is 10.5mm, and the diameter is 20μm. Next, the same welding process as the lower skin is used to complete the welding with the upper skin. The adjusted high-temperature resistant inorganic glue is evenly applied between the TA15 panel and the high thermal conductivity graphene film with a thickness of 0.1mm. First, place it at room temperature for 2h, then keep it at a temperature of 60℃ for 1h, and then continue to keep it at 100℃ for 2h to complete the bonding. Finally, the whole is kept at 150℃ for 10min for stabilization.
[0128] Example 2
[0129] A directional heat-averaging composite honeycomb structure comprises a directional heat-averaging layer 3, an upper skin 11, a honeycomb core 2 and a core filler 4, and a lower skin 12 which are arranged in sequence from top to bottom, wherein the directional heat-averaging layer 3 is a graphene-based ceramic composite material with a thickness of 1 mm, the thickness of the upper skin 11 and the lower skin 12 are both 1 mm, the size of the honeycomb core 2 is a height of 10 mm and an inscribed circle diameter of 10 mm, and the filling amount of the core filler 4 is filled by volume according to the specific density.
[0130] Preparation of directional heat-saturated composite honeycomb structure:
[0131] Use 1000# sandpaper to grind the lower skin and one side of the honeycomb core to improve the roughness, then spread the brazing material between the two. The brazing material is Ti-Zr-Cu-Ni. The welding is completed in a vacuum brazing furnace. The welding process is selected at 940℃, the heat preservation time is 40min, and then at 900℃, the heat preservation time is 20min for stabilization treatment. The adjusted density is 0.8g / cm 3 The silica-based fibers are filled into the honeycomb core, the height of the honeycomb core is 10 mm, the length of the silica fibers is 10.5 mm, and the diameter is 20 μm. Next, the upper skin is welded using the same welding process as the lower skin. The graphene-based ceramic composite material is evenly sprayed onto the TA15 panel using flame spraying, and the graphene is dispersed in the dispersion medium to form a graphene dispersion with a concentration of 5%. SiO2 ceramic powder is added to the graphene dispersion with a solubility of 280 mg·L -1 , mixed evenly, wherein the spraying raw material is a mixed dispersion of graphene and SiO2 ceramic powder, the dispersion medium is deionized water, the powder particle size is 100μm, the spraying speed is 500mm / s, the spraying temperature is 800℃, the thickness is 1mm, the curing temperature is 150℃, and it is maintained for 30min. Finally, the whole is kept at 400℃ for 10min for stabilization treatment.
[0132] Comparative Example 1
[0133] A honeycomb structure without core fillers and directional heat-averaging layers comprises an upper skin 11, a honeycomb core 2, and a lower skin 12 arranged in sequence from top to bottom, wherein the thickness of the upper skin 11 and the lower skin 12 are both 1 mm, and the dimensions of the honeycomb core 2 are 10 mm in height and 10 mm in diameter of an inscribed circle.
[0134] Preparation of a honeycomb structure without core filler and directional heat-isolating layer:
[0135] Use 800# sandpaper to grind the lower skin and one side of the honeycomb core, and control the roughness within the range of 0.4 to 0.6. Then spread the brazing filler metal between the two. The brazing filler metal is Ti-Zr-Cu-Ni. The welding is completed under vacuum conditions. The welding process is 920℃, and the holding time is 20min. Then, the stabilization heat treatment is carried out at 900℃ for 20min. Next, the same welding process as that for the lower skin is used to complete the welding with the upper skin.
[0136] Table 1 Back temperature test results
[0137] Example Example 1 Example 2 Comparative Example 1 Cold noodle temperature 393.8℃ 395.2℃ 454.8℃ The difference between the 61.0℃ 59.6℃ /
[0138] Example 3
[0139] A directional heat-averaging composite honeycomb structure comprises a directional heat-averaging layer 3, an upper skin 11, a honeycomb core 2 and a core filler 4, and a lower skin 12 which are arranged in sequence from top to bottom, wherein the directional heat-averaging layer 3 is a ceramic material with a thickness of 0.1 mm, the thickness of the upper skin 11 and the lower skin 12 are both 1 mm, the size of the honeycomb core 2 is 10 mm in height and 10 mm in diameter of an inscribed circle, and the filling amount of the core filler 4 is filled by volume according to the specific density.
[0140] Preparation of directional heat-saturated composite honeycomb structure:
[0141] Use 800# sandpaper to grind the lower skin and one side of the honeycomb core to control the roughness within the range of 0.4-0.6, then spread the brazing material between the two. The brazing material is Ti-Zr-Cu-Ni. The welding is completed under vacuum conditions. The welding process is selected at 920℃ and the holding time is 20min. Then, the stabilization heat treatment is carried out at 900℃ for 20min. The adjusted density is 0.8g / cm 3 The silica fiber is filled into the honeycomb core, the height of the honeycomb core is 10mm, the length of the silica fiber is 10.5mm, and the diameter is 20μm. Next, the same welding process as that of the lower skin is used to complete the welding with the upper skin. The prepared ceramic material with a thickness of 0.1mm is connected to the upper skin by brazing. Specifically, first use 800# sandpaper to grind off the surface oxide film of the upper skin, and then lay a layer of evenly ground Ti-Cu-Ag brazing powder. Place the directional heat-absorbing layer of the ceramic material on the top layer, and apply a single-layer graphite pressure plate with a mass of 5Kg to apply the load, and then put it into a vacuum brazing furnace. At a vacuum degree of 8×10 -4 Pa, welding temperature is 890℃, holding time is 15min. Then it is lowered to 800℃, held for 5min, and cooled with the furnace until it is out of the furnace.
[0142] In the above-mentioned directional and uniformly heated composite honeycomb structure, there are many methods for preparing the ceramic material. For a clearer description, the following ceramic material preparation examples and comparative examples are provided to further illustrate.
[0143] Preparation Example 1
[0144] This preparation example provides a method for preparing a highly oriented hexagonal boron nitride ceramic material, comprising the following steps:
[0145] Weigh 8 g of large-particle flaky hexagonal boron nitride ceramic powder (average particle size of 250 μm) and 12 g of small-particle flaky hexagonal boron nitride ceramic powder (average particle size of 10 μm) in proportion; a total of 20 g of oriented ceramic powder was added to 2 L of ethanol and mechanically stirred for 1 hour;
[0146] 40 ml of graphene oxide (GO) aqueous solution (5 mg / ml) was added, and mechanical stirring was continued for 2 hours.
[0147] The mixed solution was vacuum filtered to obtain a dry mixed powder block, which was transferred to a sintering mold. The mold was placed in a muffle furnace and dried at 550°C for 2 hours under air atmosphere to obtain a boron nitride ceramic green body, which was then hot-pressed and sintered (1900°C, 30MPa, 1h) to obtain hexagonal boron nitride ceramics.
[0148] Preparation Example 2-10, Comparative Example 2-3
[0149] The differences between Preparation Examples 2-10, Comparative Examples 2-3 and Preparation Example 1 are shown in Table 2. The hexagonal boron nitride ceramics obtained from Preparation Examples 1-10 and Comparative Examples 2-3 were subjected to performance tests, and the test results are shown in Table 3.
[0150] Table 2 Parameters of Preparation Example and Comparative Example
[0151] Group Large particle size / g Small particle size / g GO solution / ml Preparation Example 1 8 12 0 Preparation Example 2 4 16 0 Preparation Example 3 2 18 0 Preparation Example 4 8 12 40 Preparation Example 5 4 16 40 Preparation Example 6 2 18 40 Preparation Example 7 8 12 80 Preparation Example 8 8 12 200 Preparation Example 9 0 20 40 Preparation Example 10 20 0 40 Comparative Example 2 0 20 0 Comparative Example 3 20 0 0
[0152] Table 3 Test results
[0153]
[0154]
[0155] It can be seen from Preparation Examples 1-6 and Tables 2 and 3 that when a graphene oxide aqueous solution is added to a large-particle-size high-oriented ceramic powder and / or a small-particle-size high-oriented ceramic powder, the IOP and thermal conductivity of the obtained hexagonal boron nitride ceramic increase, and the density gradually increases. This indicates that under the action of the graphene oxide aqueous solution, the orientation, thermal conductivity and density of the hexagonal boron nitride ceramic can be improved.
[0156] By preparing examples 1-3 and combining Figure 3-5 It can be seen that when GO solution is not added, as the content of large pieces increases, the orientation arrangement structure of hexagonal boron nitride ceramics is optimized.
[0157] By preparing examples 1, 6-8 and combining Figure 5-8 It can be seen that when the weight of large-particle high-oriented ceramic powder and small-particle high-oriented ceramic powder remains unchanged, the orientation arrangement structure of hexagonal boron nitride ceramics is optimized with the increase of GO solution content.
[0158] Preparation of directional heat-saturated composite honeycomb structure:
[0159] The ceramic materials prepared in the above-mentioned Preparation Examples 1 to 10 were respectively applied to the oriented and uniformly heated composite honeycomb structure in Example 3.
[0160] Performance test: Back temperature experiment, the directional heat-averaging layer honeycomb surface of the above-mentioned Preparation Examples 1 to 10 and one side of the honeycomb in Comparative Example 1 were heated to 700°C, and the temperature of the other side was tested. The results showed that compared with the comparative honeycomb structure without core filling and directional heat-averaging layer, the cold surface temperature measured by the directional heat-averaging layer honeycomb structure applied in Preparation Examples 1 to 10 was at least 60°C lower than the cold surface temperature of 454.8°C measured in Comparative Example 1, and had better heat resistance.
[0161] One of the ceramic materials prepared in the above-mentioned Preparation Examples 1 to 10 is selected and applied to the oriented heat-equalizing honeycomb structure in Example 3. A highly oriented hexagonal boron nitride ceramic material prepared in Preparation Example 1 is selected. Its operation process is simple, and the step of adding graphene oxide (GO) aqueous solution is omitted, and its thermal conductivity test also performs well. Its radial thermal conductivity is 153.21W / m·K, that is, the heat flux per unit area and unit temperature difference in the radial direction is 153.21W. This value is relatively high, indicating that the thermal conductivity of the material in the radial direction is very good; the axial thermal conductivity is 13.27W / m·K, that is, the heat flux of the material under the same conditions in the axial direction is only 13.27W, which is much lower than the radial thermal conductivity, indicating that the thermal conductivity of the material in the axial direction is weak. The thermal conductivity of this material in different directions is quite different, and it can be considered as a "oriented heat-equalizing material."
[0162] Performance test: Back temperature test results are as follows Figure 2 As shown, the honeycomb surface of the oriented heat-averaging layer of the ceramic material of Preparation Example 1 in Example 3 and one side of the honeycomb in Comparative Example 1 were heated to 700°C, and the temperature of the other side (cold surface) was tested. It can be seen that, compared with the comparative honeycomb without core filling and oriented heat-averaging layer, the cold surface temperature measured in Example 3 when the ceramic material of Preparation Example 1 was oriented heat-averaging layer was 387.9°C, which was 66.9°C lower than the cold surface temperature of 454.8°C measured in the comparative example, and had better heat resistance.
[0163] The higher the thermal conductivity (W / m·K), the better the thermal conductivity. When Example 3 uses the directional heat-dissipating layer of the ceramic material of the other preparation examples mentioned above, the difference between the cold surface temperature of 454.8°C measured in the comparative example can reach 70-75°C, which has better heat resistance.
[0164] The directional heat-averaging honeycomb structure described in the present invention has an outermost directional heat-averaging layer that can avoid the aggregation and accumulation of heat on the surface to a great extent, and conduct the heat laterally to the low temperature area, thereby reducing the effective heat input per unit area in the heat concentration area on the honeycomb surface; the core filling inside the honeycomb can effectively hinder the transmission of heat inside the honeycomb through conduction and radiation effects, thereby improving the thermal capacity of the honeycomb structure, thereby reducing the effective transmission amount of honeycomb heat from the hot end to the cold end, and can effectively achieve secondary control of the introduced heat, thereby avoiding the problem of overheating failure of the protected device due to excessive introduced heat.
[0165] The use of the directional heat-homogenizing honeycomb structure of the present invention not only meets the current development trend of lightweighting, but also can effectively improve the heat resistance / insulation capacity of the honeycomb structure and the safety of the protected devices inside the honeycomb. It has the advantages of light weight, heat resistance and high insulation capacity.
[0166] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A directional heat-isolating composite honeycomb structure, characterized in that: It includes a directional heat-saturating layer, an upper skin, a honeycomb core and a core filler, and a lower skin which are arranged in sequence from top to bottom.
2. The directional heat-isolating composite honeycomb structure according to claim 1, characterized in that: The directional heat-saturating layer is made of a two-dimensional material base, including but not limited to ceramic materials, high thermal conductivity graphene films, graphene-based composite materials, and graphene-based ceramic composite materials, and has a thickness of 0.01 to 10 mm.
3. The directional heat-isolation composite honeycomb structure according to claim 1, characterized in that: The upper skin is made of one of titanium-based and nickel-based alloys, and has a thickness of 0.1 mm to 20 mm.
4. The directional heat-isolating composite honeycomb structure according to claim 1, characterized in that: The lower skin is made of one of titanium-based and nickel-based alloys, and has a thickness of 0.1 mm to 20 mm.
5. The directional heat-isolation composite honeycomb structure according to claim 1, characterized in that: The honeycomb core is a honeycomb-like grid structure with a thickness of 0.01 to 3 mm and a height of 1 to 50 mm, and is made of titanium alloy.
6. The directional heat-isolation composite honeycomb structure according to claim 1, characterized in that: The core filler has a density less than 1g / cm 3 One of the silicon-based fibers, silicon-based aerogels or graphene aerogels.
7. A method for manufacturing a directional and heat-isolated composite honeycomb structure, for preparing the directional and heat-isolated composite honeycomb structure as claimed in any one of claims 1 to 6, comprising the following steps: S1. Perform surface treatment by laying or brushing one or more layers of brazing material on the lower skin; S2. Use vacuum brazing or gas shielded brazing to first weld the honeycomb core and the lower skin together; S3, filling the honeycomb core filler into the honeycomb core mechanically and / or manually; S4. Perform surface treatment by laying or brushing one or more layers of brazing material on the upper skin; S5, welding the upper skin and the honeycomb core together to obtain a honeycomb structure; S6. Preparing a two-dimensional material-based directional heat-saturating layer on the outer surface of the honeycomb structure upper skin by spraying, brazing or bonding; S7. After the final welding of the components is completed, the whole is subjected to stabilization heat treatment.
8. The manufacturing method according to claim 7, characterized in that: In the step S1 or S4, the thickness of the solder layer is 0.01 to 3.5 mm.
9. The manufacturing method according to claim 7, characterized in that: In the step S5, the welding temperature is 450-1400° C., and the holding time is 20-60 minutes.
10. The manufacturing method according to claim 7, characterized in that: In the step S7, the heat treatment temperature is 20-100° C. lower than the welding temperature.
Citation Information
Patent Citations
Thermal insulation and noise reduction structural member and manufacturing method thereof
CN111169105A
Space radiation radiator based on aluminum honeycomb plate
CN111182774A
Preparation method of wave-absorbing composite material component
CN117962370A
Honeycomb panel
JP1990026730A
Honeycomb-sandwich plate and manufacture thereof
JP1992176640A